PROVEN MARKETABILITY SCHOOL OF BIOLOGICAL SCIENCES GRADUATES: 75% GAIN EMPLOYMENT AFTER GRADUATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 4 August 2015 – Universiti Sains Malaysia (USM) is the only university in the country that offers a specialisation in the field of Applied Biological Sciences and Management of Vectors and Parasites under the School of Biological Sciences at the undergraduate level.